(untitled) (Research, Society and Development, 2024)
Neurological emergencies are among the main occurrences in an emergency room, highlighting the particularity of demonstrating the need for a longer period of stay in the emergency service, hospitalization rate, admissions to critical patient units, in this way Physiotherapy work together with the multidisciplinary team is essential in the care of these patients. The objective of the present study was to analyze the profile of neurological emergencies and physiotherapeutic performance, in order to discuss effective conduct in physiotherapeutic care in response to this demand in the emergency room sector. This is an observational study, lasting twelve months, where we analyzed age, sex, neurological diagnostic hypothesis and the physiotherapeutic treatment that was carried out. 1619 patients were treated in the emergency unit during this period, of which 192 patients presented a neurological emergency profile, representing a percentage of 11.85% in relation to the total. Regarding the pathologies found in adult patients, 4 were more prevalent, being: Ischemic Stroke (50%), Hemorrhagic Stroke (17.7%), Seizures (13%) and Traumatic Brain Injury (13%). The physiotherapeutic approaches observed in the study demonstrated a greater focus on behaviors related to the respiratory system, and a lower prevalence of action focused on the motor system and early mobilization, which is justified by the fact that priority occurs in situations of complications that promote risks of life and are commonly prevalent in this sector, directly interfering in behaviors aimed at early mobilization.